Dilated odontoma: an unusual case report and literature review - Galvez P.; Garot E.; Bres A.; Crelier A.; Castain C.; Catros S.; Fenelon M. (EDP Sciences, 2021)
Introduction: Dilated odontoma is the most severe form of a dens invaginatus, which is a rare dental malformation resulting from an invagination of the enamel organ into the dental papilla before calcification occurs. Observation: A healthy 7-years-old girl was referred to the oral surgery department to remove an impacted odontoma causing a delayed dental eruption of the right mandibular lateral incisor (tooth 42). The patient was painless and a lingual osseous swelling was observed. A computed tomography and a 3D segmentation revealed a shell-shaped mass in the position of the right mandibular lateral incisor, showing a complex anatomy. Surgical excision was carried out under general anesthesia. Histological analysis confirmed the diagnosis of DO. Discussion and conclusion: We performed a literature review investigating 16 cases of severe forms of dens invaginatus which required extraction. It highlighted the atypical aspect of our case and the importance of 3D imaging and segmentation in contributing to the accurate diagnosis and treatment of this dental malformation.